Exploring the role of socioeconomic factors in the development and spread of anti-malarial drug resistance: a qualitative study - Anyanwu, Philip Emeka (Malar J, 2017)
BACKGROUND: Malaria remains a global health issue with the burden unevenly distributed to the disadvantage of the developing countries of the world. Poverty contributes to the malaria burden as it has the ability to affect integral aspects of malaria control. There have been renewed efforts in the global malaria control, resulting in reductions in the global malaria burden over the last decade. However, the development of resistance to artemisinin-based combination therapy threatens the sustainability of the present success in malaria control. Anti-malarial drug use practices/behaviours remain very important drivers of drug resistance. This study adopted a social epidemiological stance in exploring the underlying socioeconomic factors that determine drug use behaviours promoting anti-malarial drug resistance. METHODS: A qualitative approach, involving the use of interviews, was used in this inquiry to explore the existing anti-malarial drug use practices in the Nigerian population; and the different socioeconomic factors influencing the behaviours. RESULTS: The significant malaria treatment behaviours influenced by socioeconomic factors in this study were the practice of ‘mixing’ drugs for malaria treatment, presumptive treatment, sharing of malaria treatment course, and the use of anti-malaria monotherapies. All the rural dwellers in this study reported they have mixed drugs for malaria treatment. When symptoms were experienced, socio-economic factors, like type of settlement, income level and occupation, tended to determine the treatment behaviour and, therefore, informed and determined the experience of the illness. DISCUSSION: Social and economic contexts can influence behaviours as they contribute in shaping norms and in creating opportunities that promote certain behaviours. As shown in this study, income level and type of settlement, as structural factors, affect the decision on where to seek malaria treatment and whether or not a malaria diagnostic test will be used prior to treatment. One of the dangers of using the mixed anti-malarial drugs is that it offers a safe route for the sale of expired and fake anti-malarial drugs as the mixed drugs are not sold or dispensed in their original packets. CONCLUSIONS AND RECOMMENDATIONS: Population-wide improvements in income, education, environmental and structural conditions of rural dwellers in malaria-endemic settings will encourage behavioural change on how anti-malarial drugs are used.